EVALUATING ATTITUDES AND BEHAVIOR TOWARDS SELECTIVE COLLECTION OF WASTE IN CLUJ-NAPOCA CITY, ROMANIA - POP, Ioana Nicoleta; BACIU, Călin; BICAN-BRIȘAN, Nicoleta; MUNTEAN, Octavian-Liviu MUNTEAN; COSTIN, Dan; ROGOZAN, George Călin (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
Involvement of waste generators in selective collection of waste is one of the issues that need to be tackled within a waste management system. The questionnaire survey method is often used in investigating the behaviour, the perception, the knowledge and the attitude of population regarding different environmental issues. In this case, the questionnaire survey method is used in improving waste management process at a local level. In Cluj-Napoca, like in other Romanian cities, there is little involvement in waste management process and selective collection of waste at source. This is the issue that the paper is addressing through an online survey questionnaire applied on a sample of 425 persons living in Cluj-Napoca. The questions refer to three main aspects: degree of awareness regarding selective collection of waste at source, the accessibility of the service, and present and future personal behaviour in this sector. The answers reveal that the majority of the respondents are aware of the importance of collective selection of waste, a percent of more than 44% of them state they collect waste selectively and they highlight strengths but also weaknesses of the existing system. The chi square test identified a significant influence of age and education of the respondents and the declared behaviour on selective collection of waste and their opinion on organization of the system by public authorities. Moreover, the identified aspects can be the base of the decision making process related to waste management planning, mainly referring to selective collection of waste.